Fenomena Saham Tidur dan Kinerjanya - Erpina Desy Desy Sihombing; Supramono Supramono (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
Sleeping stocks are the stocks that are not actively traded in a certain period. The aim of this is to analyze performance of the companies whose stocks are “sleeping” in Indonesia Stock Exchange. Employing purposive sampling technique, 66 stocks were selected. The analysis of the companies’ performance was done by using market capitalization and the financial ratios that consist of return on asset ratio, return on equity and earnings per share, during 2010-2012. The result of this study showed companies with small capitalization and poor perfomance tend to have sleeping stocks.